2018
DOI: 10.1016/j.jacbts.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Prevent Hypoxia-Inducible Factor-1α Signaling Through Decreased Succinate in Diabetes

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 36 publications
2
56
0
Order By: Relevance
“…Succinate and citrate were significantly decreased in PGDM compared to controls across gestation. Previous studies in non-pregnant populations have linked succinate metabolism to endogenous insulin release [ 50 ], while decreased succinate was observed in cardiomyocytes cultured in insulin resistant conditions [ 51 ]. Decreased circulating succinate and citrate observed in women with PGDM during our study may indicate alterations in TCA cycle energetics, especially in early pregnancy, that disappear in the immediate post-partum period, although the implications this has on the placenta and fetus are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Succinate and citrate were significantly decreased in PGDM compared to controls across gestation. Previous studies in non-pregnant populations have linked succinate metabolism to endogenous insulin release [ 50 ], while decreased succinate was observed in cardiomyocytes cultured in insulin resistant conditions [ 51 ]. Decreased circulating succinate and citrate observed in women with PGDM during our study may indicate alterations in TCA cycle energetics, especially in early pregnancy, that disappear in the immediate post-partum period, although the implications this has on the placenta and fetus are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study displays succinate as a stabilizer of the hypoxia-inducible factor (HIF)-1α, which has shown to be cardioprotective during ischemia and diabetic stress. Dysfunctional cardiac FA metabolism leads to the accumulation of free FAs (FFAs) in the post-ischemic diabetic heart, which subsequently decreases the expression of succinate, an inhibitor of the HIF hydroxylase enzymes, to inhibit the activity of HIF-1α [159]. The mechanism of ischemic succinate accumulation is controversial and is proposed to involve the reversal of SDH.…”
Section: Succinate and Succinylationmentioning
confidence: 99%
“…Hypoxia-inducible factor 1-alpha (HIF-1α) is a hypoxiaactivated transcription factor that confers protective effects in hypoxic conditions (26). Studies have shown the dysregulated expression of HIF-1α under diabetic conditions (27). Testis is a relatively hypoxic tissue, and HIF-1α regulates the primary transcriptional responses to hypoxic stress in normal and transformed cells, which play an adaptive role in conferring protection against cell death in the testes (28).…”
Section: Introductionmentioning
confidence: 99%